Effects of the Covid-19 Pandemic on the Frequency of Alcohol Abuse and Clinical and Psychopathological Features - Turaev Bobir Temirpulatovich; Velilyaeva Alie Sabrievna (Genius Journals, 2022)
Many scientists have predicted that the COVID-19 pandemic could have a major impact on the mental health of the population and their behavior on alcohol abuse. There are preliminary data on the effects of the COVID-19 pandemic on anxiety, depression, sleep disorders, alcohol consumption, and mental health. In a pandemic, alcohol consumption can be used to overcome the difficulties caused by the associated abnormal conditions. The comorbidity between alcohol consumption and mood or anxiety is explained by selfmedication. Research Verification Method: Alcohol Use Disorders Identification Test, (AUDIT). Conclusion: The main reason for the increase in alcohol consumption in patients with alcoholism is the presence of young children in the family, the need to stay at home and work at home, the loss of income.
Keywords: COVID-19 pandemic; alcohol abuse; anxiety and depression